2021
DOI: 10.1128/jcm.02236-20
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neural Networks Offer Morphologic Classification and Diagnosis of Bacterial Vaginosis

Abstract: Background: Bacterial vaginosis (BV) is caused by the excessive and imbalanced growth of bacteria in vagina, affecting 30-50% of women in their lives. Gram stain followed by Nugent scoring based on bacterial morphotypes under the microscope (NS) has been considered the golden standard for BV diagnosis, which is often labor-intensive, time-consuming, and variable results from person to person. Methods: We developed and optimized a convolutional neural networks (CNN) model, and evaluated its ability to automatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…This model outperformed human healthcare professionals in terms of accuracy and stability for three diagnostic categories of Nugent scores. The deep learning model may offer translational applications in automating the diagnosis of BV with appropriate supporting hardware ( Wang et al., 2020 ).…”
Section: Bacterial Vaginosismentioning
confidence: 99%
“…This model outperformed human healthcare professionals in terms of accuracy and stability for three diagnostic categories of Nugent scores. The deep learning model may offer translational applications in automating the diagnosis of BV with appropriate supporting hardware ( Wang et al., 2020 ).…”
Section: Bacterial Vaginosismentioning
confidence: 99%
“…By transmission electron microscopy, Kim et al revealed that the peptidoglycan (PG) layer in the cell wall of L. iners was thin enough to give an apparent Gram-negative morphology (Kim et al, 2020). This morphological characteristic and Gram-staining property of L. iners are clinically very important to consider, as Nugent scoring, which is based on the Gram-staining of vaginal smears, remains a common diagnostic tool in the assessment of vaginal health (Wang et al, 2021). The Gram-negative property of L. iners masks the fact that it is a Lactobacillus species and this may lead to the misdiagnosis of BV, which is a condition characterized by the depletion of Lactobacillus species in Gram-stained vaginal smears under microscopy (Vaneechoutte, 2017).…”
Section: Culture Characteristics and Gram-staining Propertiesmentioning
confidence: 99%
“…Applying this Gram-stain-based diagnostic criteria, the above-mentioned three common types of vaginal infection can be diagnosed on the same Gram-stained smear simultaneously, which improves the diagnostic efficiency and has good feasibility and generalizability. Recently, AI diagnosis of infectious diseases based on Gram stain has become an emerging interdisciplinary technology [ 25 , 38 ]. The proposal and application of these diagnostic criteria will lay a foundation for developing AV artificial intelligence diagnostic models.…”
Section: Discussionmentioning
confidence: 99%
“…Gram-stained smears can be magnified 1000 times to identify bacteria under ordinary optical microscopes and can be easily stored for a long time [ 24 ]. Moreover, diagnostic methods based on Gram staining make AI diagnosis possible [ 25 ]. Whether Gram-stained smears can follow the original wet-mount scoring system to diagnose AV remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%